Implementasi Manajemen Berbasis Sekolah di SD Negeri 29 Air Tambang - Rini Syevyilni Wisda (STAI Terpadu Yogyakarta, 2021)
The purpose of this study is to see how the implementation of school-based management is viewed from 1) Management of Curriculum Implementation, 2) management of facilities and infrastructure, 3) Management of students, 4) management of educators and 5) management of building school-community relations. Looking at the inhibiting and supporting Faktors for the implementation of SBM at SDN No. 29 Air Tambang. The method used is a qualitative method with a descriptive approach. The research instrument used interview guidelines. The results of this study were obtained after conducting research that the implementation of school-based management at SDN no 29 has been running in accordance with the stages of SBM by considering paying attention to, and reading the need to see the opportunities owned by the school, as seen from the results of the implementation of 1) curriculum implementation management it has been implemented seen from the performance of teachers from the principal working together in the implementation of the curriculum 13 , 2) the management of facilities and infrastructure has been carried out with the fulfillment of PBM supporting infrastructure, 3) the management of students has been implemented, it can be seen from the process of accepting new students according to the standards set 4) Management of educators and education staff has been implemented, it can be seen from the procurement process, and placement and improvement of teacher competencies, and 5) Management of building school relations with the community is carried out through involving the community and committees to be involved in school programs.